2020
DOI: 10.1155/2020/8899888
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Inversion Analysis of Structural Layer Modulus of Semirigid Base Pavement considering the Influence of Temperature and Humidity

Abstract: This paper is aimed to solve the overlearning problem of the neural network algorithm used to calculate the asphalt concrete pavement structural modulus in reverse. The firefly algorithm was adapted to optimize the selection of support vector machine (SVM) parameters. Based on the optimized SVM model, a new method for dynamic inversion of the semirigid base asphalt concrete pavement structural layer modulus was presented. The results show that the absolute value of relative error of each layer modulus is not m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…These loads may also have a negative impact on the operation of concrete and reinforced concrete structures to a varying degree. Therefore, in order to assess possible risks that may arise as a result of the occurrence of dynamic loads, a thorough dynamic diagnostics of such structures is needed [46,57,70,71]. After its completion, appropriate guidelines and operating conditions for such structures should be proposed.…”
Section: Dynamic Loads In Concrete Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…These loads may also have a negative impact on the operation of concrete and reinforced concrete structures to a varying degree. Therefore, in order to assess possible risks that may arise as a result of the occurrence of dynamic loads, a thorough dynamic diagnostics of such structures is needed [46,57,70,71]. After its completion, appropriate guidelines and operating conditions for such structures should be proposed.…”
Section: Dynamic Loads In Concrete Structuresmentioning
confidence: 99%
“…However, the results presented in [50] relate to concretes subjected to static loads only. However, it should be emphasized that the situations when it is necessary to take into account dynamic loads in the analyses of concrete structures are numerous, e.g., [51][52][53][54][55][56][57][58][59][60][61]. Their summary is presented in detail in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic modulus of polyurethane foam samples fluctuated near the initial value with an increase in the soaking time and did not significantly change with soaking time. A few scholars [ 80 , 81 , 82 , 83 ] studied the physical properties of polyurethane foam materials in frozen soil environments and found that the water absorption increased with the increase in soaking time. Figure 5 summarizes the change in the moisture absorption rate of foam materials with soaking time.…”
Section: Effect Of Water Environment On the Polyurethane Foams Materi...mentioning
confidence: 99%
“…Compared to the influence of temperature fields, the study concerning the influence of humidity fields was insufficient, and humidity fields are not considered in the current concrete pavement design and calculation [ 8 ]. Nevertheless, with the continuous deepening of research on the impact of early stage behaviors, it has been recognized that humidity had a significant impact on the deformation and stress of the pavement slabs [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Rania E. Asbahan et al [ 21 ] measured the curvature of concrete slabs caused by humidity strain after 1–2 years through experiments.…”
Section: Introductionmentioning
confidence: 99%